Iqbal's ideas on man & personality - Abdul Razak, Mohd Abbas (s.n, 2012)
This research is an attempt to explore the philosophical ideas of Muhammad Iqbal (1877-1938) with regards to man and personality. Iqbal, who had a strong Islamic background, promoted many positive ideas on man and on the latent powers of the human psyhe